2003
DOI: 10.1053/jhep.2003.50039
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar hypertrophy correlates with hepatocellular carcinoma development in cirrhosis due to HBV infection

Abstract: Patients with cirrhosis are at significant risk for hepatocellular carcinoma (HCC). The aim of the present study was to evaluate the relationship between the percentage of hepatocytes showing nucleolar hypertrophy and the development of HCC in cirrhosis of different causes. A total of 111 cirrhotic patients were studied, with a mean follow-up period of 83.3 months. Histologic sections from liver biopsy specimens were silver stained for selective visualization of the nucleolus; the nucleolar area was measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…59 Interestingly, there is evidence that, as far as chronic liver diseases from viral infections are concerned, an up-regulation of hepatocyte ribosome biogenesis is constantly associated with later onset of HCC. 60,61 Both hepatitis B (HBV) and hepatitis C (HCV) viruses, which are responsible for the development of chronic liver disease, have been shown to up-regulate the activity of the RNA polymerase I and III. 62,63 The HBV X protein, required for viral replication and correlated with the hepatocarcinogenesis of individuals chronically infected with HBV, modulates RNA polymerase I-dependent rRNA transcription by enhancing the rRNA promoter activity, 62 and activates specific RNA polymerase III-dependent promoters.…”
Section: Nucleolar Functional Up-regulation As a Risk Factor In Develmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Interestingly, there is evidence that, as far as chronic liver diseases from viral infections are concerned, an up-regulation of hepatocyte ribosome biogenesis is constantly associated with later onset of HCC. 60,61 Both hepatitis B (HBV) and hepatitis C (HCV) viruses, which are responsible for the development of chronic liver disease, have been shown to up-regulate the activity of the RNA polymerase I and III. 62,63 The HBV X protein, required for viral replication and correlated with the hepatocarcinogenesis of individuals chronically infected with HBV, modulates RNA polymerase I-dependent rRNA transcription by enhancing the rRNA promoter activity, 62 and activates specific RNA polymerase III-dependent promoters.…”
Section: Nucleolar Functional Up-regulation As a Risk Factor In Develmentioning
confidence: 99%
“…A series of studies performed to define whether nucleolar changes might be related to neoplastic transformation in chronic liver disease from viral infection demonstrated that the presence of abnormally enlarged hepatocyte nucleoli represent a very strong risk factor for developing HCC, mainly in the HBV-related cirrhotic livers. 61 In other words, only those chronic liver lesions in which the viral infection induced hypertrophy, and consequently a functional up-regulation of nucleoli, would be susceptible to cancer development.…”
Section: Nucleolar Functional Up-regulation As a Risk Factor In Develmentioning
confidence: 99%
“…The 5-year cumulative HCC incidence in cirrhosis is between 10% and 30% in HBV and HCV infection, depending on the geographic region, approximately 20% in hereditary hemochromatosis and 8% in alcoholic cirrhosis (Fattovich et al, 2004). Predictors of HCC in cirrhosis include the severity of liver disease determined by the ChildPugh score (Bolondi et al, 2001), the disease activity, reflected by serum transaminase activities (Benvegnu et al, 1994;Tarao et al, 1999), and some histological criteria, such as the presence of large cell changes (LCC) (Borzio et al, 1995;Ganne-Carrié et al, 1996), macronodules (Borzio et al, 2003) and markers for hyperregeneration (Donato et al, 2001;Trerè et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The findings reported here, using a T antigen transformed cell model, lay the groundwork for determining the cellular activities that are involved in increased nucleolar size and determining the relationship of nucleolar hypertrophy to transformation. Trere et al (2003) suggest that the nucleolar hypertrophy may be the result of transactivation of the RNA Polymerase I promoters by the HBX protein. However, we have shown that SV40 T antigen transactivates ribosomal promoters yet several mutants that are compromised in this activity are competent in cellular transformation (Cavender et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the tumor virus Hepatitis B (HBV) is known to enhance rRNA promoter activity, increase ribosome production, and in some cases lead to cancer (Wang et al, 1998;Cavender et al, 1999). Studies have shown that chronic viral liver diseases, such as HBV, up-regulate and enlarge nucleoli and are associated with the eventual development of hepatocellular carcinomas (Trere et al, 2003). Thus, several of these investigations suggest that increased numbers of nucleoli represent the key variable in tumor cell growth; others suggest that the predominant factor is increased nucleolar size ).…”
Section: Introductionmentioning
confidence: 99%